2015
DOI: 10.1007/s12010-015-1557-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Display of Yarrowia lipolytica Lipase Lip2p Using the Cell Wall Protein YlPir1p, Its Characterization, and Application as a Whole-Cell Biocatalyst

Abstract: The Yarrowia lipolytica lipase Lip2p was displayed on the yeast cell surface via N-terminal fusion variant using cell wall protein YlPir1p. The hydrolytic activity of the lipase displayed on Y. lipolytica cells reached 11,900 U/g of dry weight. However, leakage of enzyme from the cell wall was observed. The calculated number of recombinant enzyme displayed on the cell surface corresponds to approximately 6 × 10(5) molecules per cell, which is close to the theoretical maximum (2 × 10(6) molecules/cell). Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Cell surface display of Yarrowia lipolytica lipase using the Pir1p can be applied as a whole‐cell biocatalyst (Yuzbasheva et al . 2015). Xylose reductase fused with Pir4 in the Saccharomyces cerevisiae cell wall had higher thermal and pH stability than the control (Hossain et al .…”
Section: Probiotics Surface Display Systemmentioning
confidence: 99%
“…Cell surface display of Yarrowia lipolytica lipase using the Pir1p can be applied as a whole‐cell biocatalyst (Yuzbasheva et al . 2015). Xylose reductase fused with Pir4 in the Saccharomyces cerevisiae cell wall had higher thermal and pH stability than the control (Hossain et al .…”
Section: Probiotics Surface Display Systemmentioning
confidence: 99%
“…These co‐displayed whole‐cell lipases also demonstrated high biodiesel conversion (95.4%) and good operational stability . Even though cell‐bound lipases have already been shown to display higher thermal tolerance and higher tolerance to the presence of detergents in contrast to free enzyme, Huang et al . still proposed approaches, such as stepwise addition of methanol or addition of hydrophilic solvent into the reaction media, to further prevent the occurrence of lipase inactivation …”
Section: Biodiesel Production Using Whole‐cell Lipasementioning
confidence: 99%
“…The whole cells showed good stability in isooctane system where methanol was provided in a three-stepwise addition procedure to reduce lipase inactivation. Under these conditions a methyl ester reaction yield of 83.1% was obtained after 72 h. Lipase 2 from Y. lipolytica is an extracellular lipase that was displayed on the surface of the yeast to test its applications as a whole cell catalyst [178]. Results showed that the cell-bound lipase was more thermostable than the free lipase and was capable of producing biodiesel with a yield of 84.1% after 33 h. Yan et al [179] fluorescens and Candida sp.…”
Section: Methanolysis Of Jatropha Oil Gave Better Yields With the Whomentioning
confidence: 99%